Trapped in freshwater: the internal anatomy of the entoproct Loxosomatoides sirindhornae - Wanninger Andreas; Wood Timothy S; Schwaha Thomas (Frontiers in Zoology, 2010)
Abstract Background Entoprocta is a small phylum of tentacle-bearing spiralian lophotrochozoans that comprises mainly marine representatives, with only two known freshwater species. One of them, Loxosomatoides sirindhornae Wood, 2005 was only recently described, and detailed information on its morphology including adaptations to life in freshwater are unknown. We analyzed the internal anatomy of L. sirindhornae using serial semi-thin sections, 3D reconstruction, as well as immunocytochemistry and confocal laserscanning microscopy. Results The nephridial system shows high complexity, strikingly similar to that of Urnatella gracilis, the only other known freshwater entoproct. It is composed of 105-120 large flame-bulb terminal organs that occur in the stalk and calyx. In the stalk they terminate in the epidermis, whereas efferent ducts in each terminal organ in the calyx lead to large, paired terminal ducts that fuse close to the central nervous system and open into the atrium by a nephridiopore. Compared to other stolonate entoprocts, L. sirindhornae shows a different stalk-calyx junction by possessing only a single, multicellular canopy instead of a stack of star cells. A sphincter muscle is situated below the diaphragm of the stalk. The remaining musculature is concentrated in the stalk, while the calyx musculature is sparsely developed. The central nervous system is dumbbell-shaped as in basal entoprocts. Conclusions The nephridial system probably has mainly osmoregulatory function. Previous studies have shown that L. sirindhornae is unable to cope with higher salinities, suggesting that its adaptation to freshwater has reached such a high degree that it is unable to 'turn off' the nephridial system in higher salinities. The current data available show that the architecture of internal organ systems such as the musculature or the calyx-stalk junction hold more promising information for taxonomic and perhaps even evolutionary inferences in Entoprocta than external characters such as spination. Contrary to previous investigations, the longitudinal calyx musculature of the genus Loxosomatoides should not be classified as generally strong or conspicuous, since its extent and site of insertion differs between species.